Finding Candidate Options for Investment From Building Blocks to Composite Options and Preliminary Screening - Davis, Paul K. (RAND Corporation, 2008)
Description of a methodology and a prototype tool, Building Blocks To Composite Options Tool (BCOT), for identifying investment options for defense capability areas. It ensures that a broad range of options is considered initially, then uses a screening technique to narrow the range to those meriting more-extensive assessment in a fuller portfolio-analysis framework. BCOT extends classic economics and operations-research techniques and suggests pragmatic approximations, particularly in capabilities-based planning.